Screening of surfactant mixture ratio for preparation of oil-in-water nanoemulsion: A technical note - Shobhit Kumar, Karan Wadhwa, Rakesh Pahwa, Javed Ali, Sanjula Baboota (Journal of Applied Pharmaceutical Science, 2024)
In the present work, nanoemulsions were fabricated utilizing the high-energy emulsification method. The selection of the ratio of surfactant (tween 80)/co-surfactant (lauroglycol 90) mixtures (Smix) used for the preparation of nanoemulsion was done on the basis of the area occupied by Smix molecules at the interface. Amin at the interface gives the information about the molecules that adsorb at the oil–water interface pack together. The small value of Amin indicates that strong adsorption has taken place at the oil–water interface. Moreover, it indicates a close contact between oil and water too. Molecular orientations of surfactant molecules at this ratio are nearly perpendicular to the interface, providing a more close packing thereby producing a more stable nanoemulsion. A composition that contains different ratios of surfactant (tween 80)/co-surfactant (lauroglycol 90) mixtures (Smix) was prepared to achieve a small Amin value. Surface tension value was used to estimate the area per molecule and surface excess concentration. The value of Amin for Smix ratios 1:0, 1:1, 2:1, 3:1, 4:1, 5:1, 1:2, and 1:3 were found to be 0.83, 0.82, 0.70, 0.62, 0.54, 0.60, 0.86, and 0.87, respectively. Among these Smix ratios, ratio 4:1 was selected for preparing the nanoemulsion as it exhibited the low Amin required for optimum emulsification conditions. It can be inferred that the determination of Amin for Smix serves as an effective technique in the screening of Smix ratio for producing a stable nanoemulsion.
Keywords: Nanoemulsion, emulsification, surface tension, stability